Bone incineration: An experimental study on mineral structure, colour and crystalline state. (June 2019) - Greiner, M.; Rodríguez-Navarro, A.; Heinig, M.F.; Mayer, K.; Kocsis, B.; Göhring, A.; Toncala, A.; Grupe, G.; Schmahl, W.W.
Abstract: Unheated and heat-treated bovine bone material with differing heating times and heat-treated in increments from 100 °C to 1000 °C were analysed to study the crystallographic change of fresh biological bone mineral occuring during incineration. We combine several complementary analytical methods applied to the same unheated and heat treated material to ensure data consistency in order to establish a comprehensive study on heat-induced changes in bone. We applied quantitative powder X-ray diffraction, Fourier Transform Infrared Spectroscopy (FTIR), and Infrared-coupled Thermogravimetric Analysis (TGA-FTIR), and we correlated the analytical results with empirical indicators such as crystallinity indices (CI and IRSF) and bone colour changes after burning. At temperatures from 700 °C onwards after 30 min of heating, a considerable recrystallization reaction from bioapatite to hydroxyapatite occurred. FTIR revealed that there are no or only minor amounts of hydroxyl-ions in original bone mineral which in consequence should be referred to "carbonate-hydro-apatite" rather than hydroxyapatite. Thermal treatment induced a pronounced increase of crystallite size and an increase of hydroxyl groups in the apatite lattice accompanied by a depletion of water and reduction of carbonate contents during incineration. Thus, the heat treatment at temperatures ≥700 °C leads to the recrystallization of bioapatite to hydroxyapatite. Above 800 °C buchwaldite is formed from the Na component within the bone mineral. Moreover, we found that the transformation reaction involving crystallite growth mainly sets in after organic matrix compounds and their residues have been combusted and the apatite grains get into direct contact. The information in this work, obtained by a combination of analytical methods which are typically applied and approved to determine bone cremation temperatures, can help to better understand changes in complex biomaterials during heating. In particular, the knowledge from this study can be applied to assess the cremation conditions of archaeological bone finds. As changes in the bone mineral state are not only dependent on temperature but also on time, care must be taken to deduce a defined temperature which cremated bone finds were exposed to. Highlights: Bone mineral is carbonate-hydro-apatite with no or only minor amounts of OH − ions. Bioapatite reacts to hydroxyapatite with heat treatment. Buchwaldite (CaNaPO4 ) forms when bone is heated at temperatures ≥800 °C. Combustion of organics in bone accelerates crystallite growth at high temperatures.